Pengaruh Kapitalisasi Pasar, Struktur Modal dan Arus Kas Operasi terhadap Tingkat Pengembalian Saham - Sundari, Iska Ayu; Nurbaiti, Beti; Ningrum, Endah Prawesti; Nuryati, Tutty; Yulaeli, Tri (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
The basic materials sector in Indonesia experienced significant stock price volatility between 2019 and 2023, largely due to external factors such as geopolitical conflicts and global economic uncertainty. This study aims to examine the effect of market capitalization, capital structure, and operating cash flow on stock returns in basic materials companies listed on the Indonesia Stock Exchange. A quantitative approach was applied using secondary data from annual financial statements and public market data. The population includes all basic materials sector companies during the 2019 -2023 period, and purposive sampling yielded 42 firms. The study applied panel data regression using first-difference transformation and natural logarithm transformation for market capitalization to improve data stability. Model selection was conducted through Chow, Hausman, and Lagrange Multiplier tests, while classical assumption tests ensured model validity. Regression analysis using the Common Effect Model showed that each independent variable market capitalization, capital structure, and operating cash flow has a significant positive effect on stock returns. Simultaneously, the three variables jointly influence stock returns, explaining 98.3% of its variation. These findings suggest that both external (market capitalization) and internal (capital structure and operating cash flow) company factors are crucial in determining stock performance. The results have practical implications for investors and corporate managers in optimizing capital decisions and assessing company financial sustainability in volatile market conditions.